2023
DOI: 10.3390/su15032392
|View full text |Cite
|
Sign up to set email alerts
|

Flood Policy and Governance: A Pathway for Policy Coherence in Nigeria

Abstract: In recent years, Nigeria is witnessing increasing frequency of flood occurrence with devastating impact translating into significant loss of lives (in Nigeria, over 300 people died in September 2022) and properties. Addressing flood disaster requires holistic approach from policy and governance perspectives, integration of policies and programs and synergies between institutions. Using synergies and eliminating trade-offs, flood governance and policy coherence integrate all relevant policy fields and instituti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 98 publications
0
0
0
Order By: Relevance
“…Although previous studies have extensively addressed flood insurance, there is a notable lack of studies that specifically delve into the flood insurance framework within Malaysia (Wan Daud et al, 2016). Recognizing the substantial research gap, Danhassan et al (2023) have suggested that upcoming studies should concentrate on investigating flood insurance. Hence, the primary aim of this study is to analyze the flood insurance approaches employed in the United States and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have extensively addressed flood insurance, there is a notable lack of studies that specifically delve into the flood insurance framework within Malaysia (Wan Daud et al, 2016). Recognizing the substantial research gap, Danhassan et al (2023) have suggested that upcoming studies should concentrate on investigating flood insurance. Hence, the primary aim of this study is to analyze the flood insurance approaches employed in the United States and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, government policies are very important in handling flood disasters because flood disasters have a significant impact on humans, the environment, and the economy (Danhassan et al, 2023). Without appropriate government policies, efforts to deal with flood disasters can become uncoordinated and ineffective.…”
Section: Introductionmentioning
confidence: 99%